Kenyan engineering teachers building reflective practice. Issue 5 (3rd September 2021) - Radhakrishnan, Dhinesh; Capobianco, Brenda M.; DeBoer, Jennifer
ABSTRACT: This study examined reflective practice by teachers in a fragile community in Kenya. Without formal qualifications, teachers grappled with engineering teaching until they become critically reflective practitioners. We used qualitative data from weekly critical friends meetings, teacher journals, peer observations, messaging app conversations, and semi-structured interviews. Analysis entailed inductive coding to identify two themes: reflective practice enabled teachers to collaborate and develop identities. Implications suggest reflective practice is an effective tool for untrained teachers in Kenya to make meaning, build identities, and actualize their teaching and learning to meet growing demand for teacher preparation under recent curricular reforms.